Extremal loading of soft fibrous tissues: multi‐scale mechanics and constitutive modeling. Issue 1 (21st October 2015) - Linka, Kevin; Khiêm, Vu Ngoc; Itskov, Mikhail
Abstract In the current contribution, we present a multi‐scale constitutive model capturing macroscopic inelastic effects (like stress softening and permanent set) in soft tissues under cyclic loading. Soft biological tissues can be described as a biological composite material. The extracellular matrix is hereby reinforced by collagen fibers which themself are an assembly of collagen fibrils embedded in a proteoglycan (PG) rich matrix. Micro‐damage induced by cyclic loading is treated by an interaction scenario between the fibrils and the PGs. At the low strain regime PGs promote sliding between fibrils [1] which leads to the yielding of statistical distributed overlapping segments. The breakage of the PG‐bridges is defined by a decreasing PG‐density. Due to the accumulated damage of the PG connections at high tissue strains, the strains at the fibril level increases. This finally drives the over‐stretching of the fibrils, which is associated with a permanent rupture of the hydrogen bonds inside of the tropocollagen molecules [2]. The so obtained model is in line with recent experimental findings [1, 2] and was additionally validated against experimental data available in literature. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)